Protein interactors of AtSR1 mRNA during salt stress - Burjoski, Vesper, author; Reddy, Anireddy, advisor; Bedinger, Patricia, committee member; Prasad, Ashok, committee member; Snow, Chris, committee member (Colorado State University. Libraries, 2021)
To survive adverse conditions, plants must respond physiologically to biotic and abiotic stresses. Stressors are detected via primary sensors in the cell wall and plasma membrane to elicit a host of secondary signals, such as reactive oxygen species and calcium (Ca2+) flux. These secondary messengers are detected by a host of signal transduction molecules for the modulation of gene expression and physiology in response to stress. In the case of calcium, the class of proteins known as calmodulin and calmodulin-like proteins bind calcium and this complex then interacts with many proteins, including transcription factors, to activate the stress response. One calmodulin-binding protein, known as Signal Responsive 1 (SR1) or CAMTA3, is known to play a role in diverse stress response pathways, including basal plant immunity, systemic acquired resistance, cold, herbivory, and salt stress, acting as both a positive and negative regulator of resistance depending on the stress. SR1 mRNA accumulates several-fold during salt stress due to increased stability mediated by reactive oxygen species (ROS). This accumulation requires the 3' end of the transcript and is not accompanied by corresponding increases in SR1 protein. Thus, the physiological mechanism and role of SR1 accumulation during salt stress poses an important question in understanding how SR1 mediates salt stress response. I hypothesized that a protein factor might bind SR1 during salt stress, possibly after undergoing an ROS-triggered conformational change to increase its RNA binding capacity, to confer increased stability to SR1, likely by protecting it against deadenylase-mediated degradation. Here, I describe my studies to test this hypothesis. I created transgenic lines of Arabidopsis expressing SR1 fused to an N-terminal protein tag (3xFLAG) and a 3' RNA aptamer tag (MS2) and used these lines to perform MS2 tandem repeat affinity purification and mass spectrometry, or MS2-TRAP-MS. In the presence and absence of salt, Arabidopsis WT and transgenic seedlings were exposed to UV radiation to crosslink the RNA population to directly interacting proteins, then ground to powder in liquid nitrogen and lysed. The lysate was passed over amylose beads bearing the MS2 coat protein (MCP), which binds the MS2 RNA aptamer, to pull down SR1-MS2 and any crosslinked proteins. RNA was removed from the population of crosslinked proteins via RNAseI digestion, and the proteins were separated on SDS gels for use in liquid chromatography mass spectrometry (LC-MS). Across all experiments and samples, LC-MS identified 395 individual Arabidopsis proteins. In the salt-treated sample, GO term enrichment revealed significantly higher prevalence of metabolically related terms, and the salt-treated sample also showed a much higher proportion of proteins predicted to be localized to the mitochondria or chloroplast. Among these proteins, only 2 were reproducibly enriched as interacting with SR1-MS2 under salt treatment: glutamate dehydrogenase 2 (GDH2) and rubisco bisphosphate carboxylase large chain (rbcL). Both GDH2 and rbcL are multimeric metabolic enzymes: GDH2 is a mitochondrial enzyme involved in nitrogen metabolism, and rbcL is a chloroplastic enzyme that catalyzes the carboxylation of ribulose bisphosphate during photosynthesis and makes up a significant portion of a plant cell's total protein. These surprising results are discussed and evidence is amassed leading us to conclude that my results may represent real binding of SR1-MS2, despite the unexpected nature of the enriched proteins and the high prevalence of rbcL. Both GDH2 and rbcL are known to possess some RNA binding capacity, and it is possible that SR1-MS2 plays a role in competing with their other RNA binding targets under salt stress. It is also possible that SR1-MS2 and its interactions with these proteins play a role in the stabilization of liquid-liquid phase separation in the organelles upon salt stress-induced destabilization of organellar condensates. Further experiments are needed to conclusively show that this binding is not artifactual, including yeast three-hybrid verification of the interactions, gel shift assays, and visualization of SR1-MS2 localization during salt stress.